Korelasi Pola Asupan Protein Dan Zat Besi Dengan Kadar Hemoglobin Pada Mahasiswi Prodi Kedokteran Universitas Khairun - Amran Nur; Rafli Ardiansyah; Jasmawati Jasmawati (UNIVERSITAS MUHAMMADIYAH MATARAM, 2024)
Iron Deficiency Anemia (IDA) is anemia with the cause being a decrease in the amount of iron needed in the process of erythropoiesis due to depleted iron stores, causing a decrease in hemoglobin formation. Riskesdas data in 2018 stated that in 300,000 households, women experienced more anemia (27.2%) than men (20.3%). The anemia rate among 15-24 year olds reached 32% in 2018. Knowing the correlation of protein and iron intake patterns with hemoglobin levels in Khairun University Medical Study Program students. This research is an analytic study that uses a cross-sectional approach. The research sample was female students who met the inclusion criteria and were determined using purposive sampling technique. Data on protein and iron intake patterns were collected through interviews using the 24-hour food recall method taken twice. Data on hemoglobin levels were obtained from collection with a portable Hb meter. In 109 samples, the most common results were deficient protein intake (78.0%), deficient iron intake (75.2%), and normal hemoglobin (72.5%). and methodology are arranged in the form of past tense, while the results and conclusions in the form of simple present tense.